Acute pancreatitis in pregnancy: 5-year experience from a multidisciplinary centre - Srikumar, Saranya; Nair, Sobha S.; Reghunath, Reshma; Raj, Saranya; K., Radhamany (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Acute pancreatitis is rare in pregnancy, but it is associated with increased incidence of maternal and fetal mortality. It should be one of the differential diagnosis of upper abdominal pain with or without nausea or vomiting. S. amylase, lipase and ultrasound abdomen were the diagnostic methods. Conservative management is the main stay in mild cases. Severe cases have multiorgan involvement and needs multidisciplinary approach. The objectives of this study were to study the maternal and fetal outcome in pregnant women diagnosed with acute pancreatitis and to identify the risk factors for acute pancreatitis in pregnancy. Methods: Retrospective descriptive study of pregnant women diagnosed with acute pancreatitis in Amrita Institute of Medical Sciences, Kochi during the period of 5 years from January 2011 to December 2016. A proforma having patients age, parity index, gestational age, symptoms with duration, blood investigations, ultrasonography, interventions done, mode of delivery, supportive treatment, complications were developed. Fetal weight, Apgar score, fetal complications were also noted. Results: The mean gestational age of presentation was 30 weeks of pregnancy. Upper abdominal pain radiating to back, vomiting, fever was the commonest clinical presentation in majority of cases. The diagnostic methods were S.Amylase ,Lipase and Ultrasound abdomen. The mean age of the patients were 26 years and 66.7% were primigravidas in the present study. There were 4 patients in SAP and 5 in MAP groups. Complications in SAP group were ARF, ARDS, DIC, MODS, metabolic acidosis etc. SAP group had 3 maternal and 3 fetal loss. Conclusions: Severe acute pancreatitis has adverse maternal and fetal outcome due to multi organ failure and sepsis.